Technique of ICP Monitored Stepwise Intracranial Decompression Effectively Reduces Postoperative Complications of Severe Bifrontal Contusion - Sun, Guan; Shi, Lei; Pan, Tianhong; Li, Xiaoliang; Zhang, Shuguang (Frontiers in Neurology, 2016)
Background Bifrontal contusion is a common clinical brain injury. In the early stage, it is often mild, but it progresses rapidly and frequently worsens suddenly. This condition can become life threatening and therefore requires surgery. Conventional decompression craniectomy is the commonly used treatment method. In this study, the effect of intracranial pressure (ICP) monitored stepwise intracranial decompression surgery on the prognosis of patients with acute severe bifrontal contusion was investigated. Method A total of 136 patients with severe bifrontal contusion combined with deteriorated intracranial hypertension admitted from March 2001 to March 2014 in our hospital were selected and randomly divided into two groups, i.e., a conventional decompression group and an ICP monitored stepwise intracranial decompression group (68 patients each), to conduct a retrospective study. The incidence rates of acute intraoperative encephalocele, delayed hematomas, and postoperative cerebral infarctions and the Glasgow outcome scores (GOSs) 6 months after the surgery were compared between the two groups. Results (1) The incidence rates of acute encephalocele and contralateral delayed epidural hematoma in the stepwise decompression surgery group were significantly lower than those in the conventional decompression group; the differences were statistically significant (P < 0.05); (2) 6 months after the surgery, the incidence of vegetative state and mortality in the stepwise decompression group were significantly lower than those in the conventional decompression group (P < 0.05); the rate of favorable prognosis in the stepwise decompression group was also significantly higher than that in the conventional decompression group (P < 0.05). Conclusion The ICP monitored stepwise intracranial decompression technique reduced the perioperative complications of traumatic brain injury through the gradual release of ICP and was beneficial to the prognosis of severe traumatic brain injury treatment.